Analisis Harga Dalam Praktek Pembulatan Harga Dalam Perspektif Ekonomi Islam - Sari, Tita Zurnila; Alfiah, Esti; Pramadeka, Katra (Al-Intaj : Jurnal Ekonomi dan Perbankan Syariah, 2023)
The purpose of this study is to determine the mechanism used in determining the selling price and services on Copy Fitri Kel. Nusa Indah Kec. Ratu Agung City of Bengkulu, as well as studying the Islamic economic perspective on the mechanism for setting selling prices and services on Photocopy of Fitri. In order to comprehensively investigate this issue, the researchers used a qualitative methodology to collect pertinent data during the study. Research data collection was carried out through the use of observation and interviews, with the aim of investigating Copy Fitri as a research subject. Research on the analysis of the pricing mechanism and Copy Fitri services reveals that the rounding off price mechanism is ambiguous. However, Foto Copy Fitri uses a fair price approach which is in line with Islamic economic principles. The pricing strategy applied by Copy Fitri is considered reasonable because it does not exploit buyers, and profit margins are maintained at a reasonable level. Fitri's photocopy does not use the rounding price mechanism, while the rest of the rounding is allocated for mosque charity. The round price is an important balance point mutually agreed upon by sellers and buyers, indicating a balance between the forces of supply and demand.